On Agrotechnical Methods for Creating Cultivated Pastures - Sobitjon, Adilov; Himail , Khalilov; Kholmurod , Bozorov (American Journal of Biology and Natural Sciences, 2025)
The article presents the results of a study to determine the area of plant nutrition, one of the most important agrotechnical techniques used in the creation of cultivated pastures with desert wheatgrass and Khorasan sainfoin, which are considered nutritious feed for livestock. When creating cultivated pastures using wheatgrass and sainfoin, an important role is played by the correct determination of the area of plant nutrition, which allows increasing pasture yields several times, enriching the vegetation cover of pastures with new species with high feed qualities, and creating conditions for guaranteed hay harvesting for wintering.